Collagen VI antibody reduces atherosclerosis by activating monocyte/macrophage polarization in ApoE−/− mice - Liu, Xianyan; Su, Jinyu; Zhou, Hui; Zeng, Zhiyun; Li, Zhonghao; Xiao, Zhi; Zhao, Ming (International immunopharmacology, 2022)
•COL6A6 protects against AS and may be an AS-protective antigen.•CVI mAb regulates monocyte and macrophage polarization.•CVI mAb reduces AS by regulating the immune system and inhibiting inflammation. Atherosclerosis (AS) has been regarded as an autoimmune disease. However, studies on immunotherapy against AS are limited. We previously found that IgG in AS patients serum binding to alpha 5 and 6 chain of collagen VI (COL6A5 or COL6A6) was significantly higher than that in healthy subjects, here we tried to identify whether they are AS-protective, and tried to develop human antibodies against them. ApoE−/− mice were immunized with COL6A5 or COL6A6 and COL6A6 was found a protective antigen against atherosclerosis. A phage display human single-chain antibody (scFv) library was constructed and COL6A6-specific scFv was obtained, and cloned into a modified pcDNA3 vector to express full-length human antibodies. ApoE−/− mice were fed a high-fat diet (HFD) for 20 weeks and administered three weekly injections of CVI monoclonal antibody (mAb) or isotype control antibody, CVI mAb was found to be able to reduce plaque area by 45 % via aorta oil red O staining. Flowcytometry method predicted that CVI mAb induced monocyte/macrophage polarization from M1 to M2. Furthermore, CVI mAb induced decreases of pro-inflammatory cytokines of MCP-1and IL-1β, and increases of IL-4 and IL-10 levels in animal serum by using theLuminexassay. Overall, we found a novel atherosclero-related antigen – Collagen VI, and its protective fragment - Collagen VI alpha 6 chain (COL6A6) and proved that humanized antibody against COL6A6 therapy regresses atherosclerosis and induces monocyte/macrophage polarization from M1 to M2 in ApoE−/− mice animal model.